ЭКОМОРФОЛОГИЧЕСКИЕ КОНВЕРГЕНЦИИ И ЭКОМОРФОЛОГИЧЕСКАЯ СИСТЕМА ОРГАНИЗМОВ - (:unkn) unknown (Киев : Наукова думка, 1984)
Рассматриваются принципы построения общей системы экоморф организмов, дается ее определение и обсуждается ее логическая и терминологическая структуры. Обосновывается крупная иерархическая структура системы в пределах трех высших рангов ее таксонов и приводятся краткие диагнозы для всех 15 конкретных таксонов этих рангов.
Ecomorphological convergences and the ecomorphological system of organisms
Principles are considered for constructing the general ecomorphological system of organisms, with the system definition given and its logical and terminological structures discussed. The large hierarchic structure of the system is substantiated for three highest ranks of its taxons. Brief diagnosis are given for all 15 specific taxons of these ranks.